Manufacturing Planning and Production Cost of a Potato Cutting Machine: Perencanaan Produksi dan Biaya Produksi Mesin Pemotong Kentang - Muhammad Fiky Dharmawan; Mulyadi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Manufacturing engineering integrates product design, machining processes, and production system management to transform raw materials into functional products. Specific Background: Potato cutting machines are utilized to support the processing of potatoes into uniform stick-shaped products, requiring appropriate manufacturing planning to ensure proper machine construction and operation. Knowledge Gap: Limited information is available regarding detailed manufacturing process planning and production cost estimation for a potato cutting machine driven by an electric motor. Aims: This study aims to determine suitable machining processes for manufacturing a potato cutting machine and to estimate the production cost required for its fabrication. Results: The planned manufacturing sequence consists of material cutting, welding, grinding, drilling, and assembly processes. The machine comprises a frame, electric motor, gearbox, pulleys, shafts, and cutting blades with specific operational functions. Manufacturing time is estimated at 15–23 hours, while the total material cost is Rp 2,518,500 and the production cost is Rp 3,453,125 per unit. Novelty: This study provides an integrated manufacturing planning framework that combines machining process identification, production time estimation, component specification, and production cost calculation for a stick-shaped potato cutting machine. Implications: The findings can serve as a reference for manufacturing planning, production budgeting, cost evaluation, and pricing decisions for small-scale machine fabrication projects.Highlights: Five fabrication stages were identified, including cutting, welding, grinding, drilling, and assembly. Total processing duration was estimated at 15–23 working hours for one unit. Material expenditure reached Rp 2,518,500, while unit fabrication cost was calculated at Rp 3,453,125. Keywords: Manufacturing Planning; Potato Cutting Machine; Machining Process; Production Cost; Electric Motor